Post-typhoid fever exudative retinal detachment - Harshvardhan M Raghuwanshi; Roshani Thakur; Amit S. Nene; Smitesh Shah; Onkar H. Pirdankar (Journal of Clinical Ophthalmology and Research)
The ocular manifestations following fever are often under-recognized; however, it can lead to significant ocular morbidity if not diagnosed early and treated timely. Post-typhoid retinitis is relatively common and has been reported previously. Here, we report a rare case of 46-year-old male diagnosed with a post-typhoid bilateral exudative retinal detachment.